Revolutionizing Artificial Organs: Next-Generation Membrane Technologies for Precision Medicine and Global Health - Jennifer S; Mehak Khanum; Ehsan Mohebi; Zaid Khan (International Journal of Membranes, 2025)
Membrane technology has emerged as a cornerstone in the advancement of artificial organ systems, offering critical functionalities in selective molecular filtration, tissue scaffolding, and controlled therapeutic delivery. Recent innovations have propelled the field beyond traditional polymeric membranes to include nanostructured, biomimetic, and stimuli-responsive materials, significantly enhancing biocompatibility, selectivity, and durability. The integration of smart technologies, such as AI-driven membrane design, bioelectronic sensors, and personalized fabrication via 3D printing, is ushering in a new era of intelligent, adaptive, and patient-specific artificial organs. Despite these achievements, significant challenges remain, including membrane fouling, long-term degradation, immune responses, regulatory hurdles, and economic barriers to widespread adoption particularly in low-resource settings. Interdisciplinary collaboration among materials scientists, engineers, clinicians, and data scientists is increasingly vital for translating laboratory advances into clinically viable solutions. Sustainable and scalable manufacturing approaches, coupled with a focus on global health equity, are essential to ensuring that next-generation membrane-based artificial organs are accessible to diverse patient populations. Looking forward, the field is poised for transformative growth, with milestones anticipated in AI-guided design, eco-friendly materials, wearable organ support devices, and equitable distribution models. This review provides a comprehensive overview of current technologies, addresses prevailing challenges, and proposes a strategic roadmap for the continued evolution of membrane technology in artificial organs, with the goal of improving patient outcomes and addressing global healthcare needs.
Keywords: 3D printing; AI-driven membrane design; Artificial organs; Nanostructured Membranes; Personalized medicine; bioartificial organs; biocompatibility; bioelectronics; biomimetic membranes; drug delivery systems; global health; hemodialysis membranes; interdisciplinary collaboration; membrane technology; regulatory challenges; scalable manufacturing; smart membranes; sustainable membranes; tissue engineering; wearable dialysis